Views on Socialism in A. Maceina’s and P. Jakas’ Works - Pruskus, Valdas (Problemos, 1982)
The views of A. Maceina and P. Jakas, Lithuanian bourgeois Catholic modernists, on the scientific theory and practice of socialism are evaluated. Their efforts to bring to the forefront in socialism not socio-economic relations, but the features of outlook and psychology are being criticized. Though A. Maceina and P. Jakas, like West-European Catholic modernists, did not categorically deny socialism, they carried on polemics with it that was being done rather with fear of the historical reality than with any liking for socialism. Distorting socialism they actually supported the capitalist system.